Polyphenols and antioxidant properties of extracts from Mentha pulegium L. and Matricaria chamomilla L. - Seddik, Khennouf; Dalila, Benchiekh; Saliha, Djidel; Saliha, Dahamna; Smain, Amira; Noureddine, Charef; Abderahmane, Baghiani; Daoud, Harzallah; Lekhmici, Arrar (Pharmacognosy Communications)
Introduction: Mentha pulegium L. and Matricaria chamomilla L. are used in the Algerian folk medicine. This study was carried out to determine the antioxidant activity of these plants and their polyphenols contents. Methods: The antioxidant capacity of the plant extracts was determined by the scavenging activity against 1,1-diphenyl- 2-picrylhydrazyl (DPPH) and β-carotene/linoleic acid model system. Total phenolic content in these extracts were determined using Folin–Ciocalteu’s reagent. Results: The methanolic extract (MeE) of Mentha pulegium L. showed the highest yield of extraction (14.4%). Whereas, the aqueous extract (AqE) of Matricaria chamomilla L. had the highest yield (18.56%) from total extracted plant material. Moreover, the ethyl acetate extract of Mentha pulegium L. contains high amount of total polyphenols; tannins and flavonoids (191.99 μg gallic acid equivalent/g dry extract; 265.33 μg tannic acid equivalent/g dry extract; 110.37 μg quercetin equivalent/g dry extract; 151.11 μg rutin equivalent/g dryextract) respectively. This extract possessed high antioxidant activity (IC50=0.017 mg/ml) in the DPPH assay whilst the chloroformic extract (ChE) is more efficient in the β carotene/linoleic acid assay with (61.07%). The ChE of M. chamomilla contains the higher value of flavonoids (197.43 μg quercetin equivalent/g) and total polyphenols were abundant in MeE. The ethyl acetate extract of this plant had the highest antioxidant activity (IC50= 0.0111 mg/ml) in the DPPH assay, while chloroformic extract shows appreciable inhibition value (37.15%) in the β carotene/linoleic acid assay. Conclusion: These results provide useful information about the utilization of these plants as natural antioxidants in food and in folk medicine.
Keywords: Antioxidants; polyphenols; Mentha pulegium; pennyroyal; Matricaria chamomilla; chamomile